Gender stereotyping and its impact on perceived emotional leadership in the hospitality industry: A mixed-methods study. (June 2022) - Xiong, Wei; Chen, Shiyun; Okumus, Bendegul; Fan, Fang
Abstract: Gender stereotyping has brought enormous challenges to organizational human resource management, and scholars and practitioners have devoted efforts to weaken or even eliminate the negative effects of masculine stereotypes on female workers. However, feminine stereotypes are not well understood, and the opportunity for femininity as a leadership trait in certain fields begs further empirical examination. For that reason, this study breaks down the single gender-leadership stereotype of masculinity, extending the gender-emotion stereotype of femininity to explore androgynous cues for employees' perceived emotional leadership (PEL) in hospitality. By conducting three studies—two Implicit Association Tests with 124 participants and a study with 466 participants—we verified the effect of gender stereotypes on hospitality leadership traits and emotional traits. The findings show that employees with different ideal gender roles of leadership (IGRL) have different degrees of PEL and employees with androgynous IGRL have higher PEL. Overall, this study suggests the necessity of androgynous leadership role and androgynous management styles in hospitality workplaces.